The influence of brand image, product quality, and price on customer satisfaction of Wardah beauty products - Indriyani, Furi; Hendarsih, Ida; Mardewi , Tati; Dewi, Nurmala (International Journal of Applied Finance and Business Studies, 2026)
This study aims to investigates the influence of brand Image, product quality, and price on customer satisfaction of Wardah Beauty Products in Bogor. The research uses a quantitative approach to analyze the relationship between independent variables and dependent variables. The sampling technique used in this study is convenience sampling, which allowed the researcher responses from individuals who were easily accessible and willing to participate. The population of this research consist of consumers residing in Bogor and have used wardah beauty products at least once prior to this study. The number of samples was 100 respondents. Data were collected through an online questionnaire distributed using google form links shared via social media platforms, particularly WhatsApp. The data analysis technique used multiple regression analysis to determine the significance and direction relationship among the variable studied. The results demonstrate that brand image, product quality, and price have a positive and significant influence on customer satisfaction of Wardah Beauty Products.